2019
DOI: 10.1056/nejmoa1809983
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Delayed-Start Trial of Levodopa in Parkinson’s Disease

Abstract: BACKGROUNDLevodopa is the main treatment for symptoms of Parkinson's disease. Determining whether levodopa also has a disease-modifying effect could provide guidance as to when in the course of the disease the treatment with this drug should be initiated. METHODSIn a multicenter, double-blind, placebo-controlled, delayed-start trial, we randomly assigned patients with early Parkinson's disease to receive levodopa (100 mg three times per day) in combination with carbidopa (25 mg three times per day) for 80 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
163
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(198 citation statements)
references
References 16 publications
4
163
0
11
Order By: Relevance
“…A chi-square test was used to compare gender between groups. The Mann-Whitney U-test was used to compare the differences between groups in the mean change of gait score, axial score, UPDRS-II total score, and UPDRS-III total score from baseline to 36 months (Verschuur et al, 2019). The one-way repeated measures ANOVA was applied to test for an effect of DBS target and follow-up time for each score.…”
Section: Discussionmentioning
confidence: 99%
“…A chi-square test was used to compare gender between groups. The Mann-Whitney U-test was used to compare the differences between groups in the mean change of gait score, axial score, UPDRS-II total score, and UPDRS-III total score from baseline to 36 months (Verschuur et al, 2019). The one-way repeated measures ANOVA was applied to test for an effect of DBS target and follow-up time for each score.…”
Section: Discussionmentioning
confidence: 99%
“…It is used to minimize the power of expectations, which is especially important in PD . In the LEAP trial, Verschuur and colleagues reported interesting patients’ assumptions about treatment allocation (Table S6 in ref. ): nearly 75% of the delayed‐start group participants correctly guessed their allocation (vs. 38.4% of the early‐start group).…”
mentioning
confidence: 99%
“…In the LEAP trial, Verschuur and colleagues reported interesting patients’ assumptions about treatment allocation (Table S6 in ref. ): nearly 75% of the delayed‐start group participants correctly guessed their allocation (vs. 38.4% of the early‐start group). This represents a nonnegligible relative risk of correct versus not knowing or wrong assumption of 1.94 (95% confidence interval, 1.60–2.35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the ELLDOPA trial as a point of reference in an attempt to resolve the uncertainty regarding the levodopa disease‐modifying effect, Verschuur and colleagues conducted the Levodopa in Early Parkinson's Disease (LEAP) trial with a delayed‐start design. A total of 445 early‐stage PD patients were randomly assigned: 222 to the early‐start group (100/25 mg of levodopa/carbidopa 3 times per day for 80 weeks) and 223 to the delayed‐start group (placebo for 40 weeks followed by levodopa/carbidopa for the subsequent 40 weeks).…”
mentioning
confidence: 99%